Progress in Combustion Diagnostics, Science and Technology - Medwell, Paul (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The role that combustion plays in the world's energy systems will continue to evolve with the changes in technological demands. For example, the challenges that we face today are more focused on the conservation of energy and addressing environmental concerns, which together necessitate cleaner and more efficient combustion processes using a range of fuel sources. This book includes contributions to highlight the recent progress in theory and experiments, development, and demonstration of technologies and systems involving combustion processes, for the production, storage, use, and conservation of energy.